Pemanfaatan Alokasi Dana Zakat Produktif Dalam Pemberdayaan UKM Melalui Bantuan Gerobak Usaha BAZNAS Kota Surabaya - Rofi’atul Maziyah; Rosmiati; Soniatul Fitriyah; Istiqomatul Afifah; Bakhrul Huda (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
This study aims to determine whether the distribution of productive zakat funds carried out by BAZNAS Surabaya city through capital assistance and business carts can be utilized and have a positive impact on its recipients, so that indirectly this can contribute to overcoming poverty and unemployment in Indonesia, especially the city of Surabaya. The methodology used in this study uses a qualitative method with primary data sources obtained through observation and interviews with one of the implementing staff in the field of distribution of BAZNAS Surabaya city, as well as SME X and SME Y as recipients of BAZNAS cart assistance, while secondary data from literature studies. The results of this study indicate that the utilization of productive zakat fund allocations has a significant impact on SME X and SME Y in the city of Surabaya, so it can be seen that the distribution of productive zakat funds through the business cart assistance program for SMEs is very helpful in efforts to empower SMEs in the city of Surabaya.